FAKTOR-FAKTOR YANG MEMPENGARUHI KESIAPAN BERWIRAUSAHA SISWA SMKN BARABAI KABUPATEN HULU SUNGAI TENGAH KALIMANTAN SELATAN - Nurbaya, Siti (Jurnal Pendidikan Teknologi dan Kejuruan, 2012)
ABSTRACTThe purposes of this research are to investigate: 1) the entrepreneurial preparedness among the  students of Barabai Vocational High School, and 2) the effect of students’ entrepreneurial knowledge, industrial practicum experience, and achievement motivation toward their entrepreneurial preparedness for both individually and mutually. The descriptive analysis results showed that the entrepreneurial preparedness of twelfth grade students of Barabai Vocational High School was high (57.7%). The hypothesis testing results showed that there was a positive and significant effect on entrepreneurial knowledge, industrial practicum experience, achievement motivation toward students’ preparedness (F= 95.418, p= 0.000). The determination coefficient of R2 = 0.599 indicated that entrepreneurial knowledge, industrial practicum experience and achievement motivation were able to explain the variable of students’ preparedness (59.9%). Each independent variable showed a positive and significant effect on the dependent variable, i.e. entrepreneurial knowledge (t = 5.095, p = 0.000), industrial practicum experience (t = 6.123 p = 0.000), and achievement motivation (5.738 = p = 0.000).Keywords: entrepreneurial knowledge, industrial practicum experience, achievement motivation, and entrepreneurial preparedness